Diagnostic potential of a novel fluoroscopic video analysis workstation (Radwisp) in patients with acute pulmonary thromboembolisms. (14th October 2021) - Okumura, Y
Abstract: Background: Pulmonary thromboembolisms (APEs) are one of the leading causes of death, and they are increasing worldwide. Contrast-enhanced chest computed tomography (CT) is the most robust imaging tool for diagnosing APEs, but a fluoroscopic video analysis workstation (Radwisp™) was newly developed to evaluate the pulmonary circulation without using contrast medium (Figure), and it can be useful as a diagnostic device in APEs. Nonetheless, it has not been validated whether Radwisp has the potential to accurately diagnose APEs. Methods: In this study, 10 consequence suspected APE patients (male:female ratio, 1:1, mean age 68.5±16 years) in our hospital were enrolled between January 2020 and April 2021. All patients were suspected of having APEs from their symptoms and physical examinations, and therefore, were scheduled for contrast-enhanced CT and cineradiographic imaging based on standard X-rays on the same day. The cineradiographic images were taken with a 20 second breath-hold followed by breathing. The cineradiographic X-ray images were moved to the fluoroscopic video analysis workstation (Radwisp™). Blinded to the patient information and contrast-enhanced CT images, four cardiologists evaluated the presence or absence of APEs, and if APEs were diagnosed, the extent of pulmonary artery filling defects due to thrombi, solely from the Radwisp-based images. We compared the findings from the Radwisp-based images to those from the contrast-enhanced CT imaging. Results: Of a total of 10 patients, 7 were diagnosed with APEs from the contrast-enhanced CT imaging, while 3 were not. All images were created within 5 minutes and the image quality was high even during breathing. three doctors accurately diagnosed 7 patients with APEs and 3 without APEs. In all 7 patients, contrast-enhance CT imaging after treatment (rivaroxaban 30mg for average 12±4 days) identified full recovery of the pulmonary circulation over both lungs, which was correctly identified on the Radwisp image by 3 doctors. Conclusions: In this validation study, the diagnostic accuracy of the Radwisp™ for APEs was reliably high. In addition, this imaging could correctly identify filling defects in pulmonary arteries. This novel Radwisp-based imaging can be a simple and reliable diagnostic tool for identifying not only APE patients, but also the severity of the pulmonary circulation caused by thrombi, and its therapeutic effects, especially in patients with severe dyspnea and renal disfunction. Radwisp™ can enable further diagnosis of the site of embolism and determination of therapeutic effect. Further studies will be needed to obtain a consistent diagnostic accuracy of APEs in patients with other pulmonary diseases. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Paramevia Pte. Ltd